Determinant Factors of Students’ Entrepreneurial Intention: a Comparative Study - Purwana, Dedi (Dinamika Pendidikan, 2018)
The research aims to analyze the impact of entrepreneurial education along with Shapero’s theory of entrepreneurial events on students' entrepreneurial intention. The research is also addressed to compare entrepreneurial intention of students lived in Jakarta and Garut city. The research method used is a survey and causal approach. Simple random sampling was used as the technique to select sample (413 respondents) from both cities. The sample size is adjusted to the model of analysis used in structural equation modeling (SEM). The research revealed that entrepreneurship education has a significant impact on perceived desirability, perceived feasibility and perceived propensity to act. This study also found that perceived desirability, perceived feasibility and perceived propensity to act were insignificant to influence students' entrepreneurial intention. The research findings suggest an agenda regarding a modification of entrepreneurship-oriented curriculum and creating school entrepreneurial atmosphere. Suggestions for future research are discussed.